Reinforcement of Paper Documents by Different Starch Modification Processes - Jing Lang (BioResources)
Paper documents gradually deteriorate during long-term storage, accompanied by acidification and a decline in mechanical strength. To achieve both deacidification and mechanical strengthening, sodium tetraborate (Na₂B₄O₇) was used as a deacidification agent, and two starch products (enzymatically hydrolyzed starch, quaternary ammonium cationic starch) served as strengthening agents. The documents were treated either by simultaneous deacidification and reinforcement (one-step method), or deacidification followed by reinforcement (two-step method). The effects of different reinforcement treatments on the mechanical properties and pH of the paper were investigated. Accelerated aging tests (dry and wet aging tests) were conducted to evaluate the change of the mechanical performance of paper documents under optimal reinforcement conditions. Deacidification and reinforcement treatments improved the tensile index, tearing index, and folding endurance. The type of starch modification and the different deacidification and reinforcement processes influenced the mechanical strength. The surface pH values of paper documents only modified with different starches remained below 7.0. Accelerated aging tests on paper treated with different starches (both deacidified and reinforced) revealed that under high temperature and humidity conditions, the mechanical properties of paper documents deteriorated more severely. The treated paper exhibited varying degrees of relative improvement in tensile index, tearing index, and folding endurance.